2022
DOI: 10.1093/neuonc/noac022
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium magnetic resonance spectroscopy enables noninvasive metabolic imaging of tumor burden and response to therapy in low-grade gliomas

Abstract: Background The alternative lengthening of telomeres (ALT) pathway is essential for tumor proliferation in astrocytomas. The goal of this study was to identify metabolic alterations linked to the ALT pathway that can be exploited for non-invasive magnetic resonance spectroscopy (MRS)-based imaging of astrocytomas in vivo. Methods Genetic and pharmacological methods were used to dissect the association between the ALT pathway a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Deuterium metabolic imaging (DMI) is a novel MRI molecular imaging technique that can be performed with oral intake or intravenous infusion of nonradioactive 2H-labeled substrates followed by deuterium magnetic resonance spectroscopic imaging and enables noninvasive metabolic imaging of gliomas [92] . DMI has been used [6,6′-2H2]glucose to monitor flux to lactate and glx (sum of glutamine and glutamate) and to visualize tumor burden in glioblastoma patients [94] . In addition, a recent animal study demonstrated that DMI can be used to non-invasively assess alternative lengthening of telomeres (ALT)-linked modulation of glycolytic flux and to monitor response to ALT-inhibitor therapy [94] .…”
Section: Radiomics Radiogenomics and Multi-omics Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Deuterium metabolic imaging (DMI) is a novel MRI molecular imaging technique that can be performed with oral intake or intravenous infusion of nonradioactive 2H-labeled substrates followed by deuterium magnetic resonance spectroscopic imaging and enables noninvasive metabolic imaging of gliomas [92] . DMI has been used [6,6′-2H2]glucose to monitor flux to lactate and glx (sum of glutamine and glutamate) and to visualize tumor burden in glioblastoma patients [94] . In addition, a recent animal study demonstrated that DMI can be used to non-invasively assess alternative lengthening of telomeres (ALT)-linked modulation of glycolytic flux and to monitor response to ALT-inhibitor therapy [94] .…”
Section: Radiomics Radiogenomics and Multi-omics Approachesmentioning
confidence: 99%
“…DMI has been used [6,6′-2H2]glucose to monitor flux to lactate and glx (sum of glutamine and glutamate) and to visualize tumor burden in glioblastoma patients [94] . In addition, a recent animal study demonstrated that DMI can be used to non-invasively assess alternative lengthening of telomeres (ALT)-linked modulation of glycolytic flux and to monitor response to ALT-inhibitor therapy [94] . Chemical exchange saturation transfer (CEST) is a molecular MRI imaging technique that is based on applying an off-resonance that can detect very low concentrations of molecules by the presence of groups with exchangeable protons, such as hydroxyls, amides, and amines [95] .…”
Section: Radiomics Radiogenomics and Multi-omics Approachesmentioning
confidence: 99%
“…45 In preclinical animal models, Kreis, et al, showed that dynamic DMI acquisitions at 9.4T could be used to acquire quantitative and spatially resolved measurements of glycolytic flux in tumors, 15 which can be used to assess treatment response. 46 Batsios et al demonstrated DMI using [U-2 H]-pyruvate for assessing early treatment response in a preclinical model for reporting on telomerase reverse transcriptase expression via assessing the production of lactate in mice with patient-derived gliomas. 47 If successfully demonstrated, DMI at 3T would accelerate clinical translation due to the ubiquity of clinical 3T scanners.…”
Section: Deuterium Metabolic Imagingmentioning
confidence: 99%
“…In addition to the seminal DMI study in patients with glioma at 4T by de Feyter et al, multiple other sites have begun DMI studies in healthy human subjects at 3T, 43 7T 44 as well as at 9.4T 45 . In preclinical animal models, Kreis, et al, showed that dynamic DMI acquisitions at 9.4T could be used to acquire quantitative and spatially resolved measurements of glycolytic flux in tumors, 15 which can be used to assess treatment response 46 . Batsios et al demonstrated DMI using [U‐ 2 H]‐pyruvate for assessing early treatment response in a preclinical model for reporting on telomerase reverse transcriptase expression via assessing the production of lactate in mice with patient‐derived gliomas 47 …”
Section: Introductionmentioning
confidence: 99%
“…Deuterium ( 2 H) MRS (DMRS) and imaging (DMRI) of 2 H‐labeled substrates and their subsequent downstream metabolites is an emerging arena of metabolic imaging 1–28 . With small‐animal models, tail vein catheterization is a common in‐magnet route of substrate administration.…”
Section: Introductionmentioning
confidence: 99%